Incompatibility in rhizoctonia solani ag-1 ia of soybean - de Campos, Ana Paula da Silva [UNESP]; Ceresini, Paulo Cezar [UNESP] (My University, 2006)
Rhizoctonia solani anastomosis group 1 IA (AG-1 IA) is considered one of the most important pathogens affecting soybean in Brazil, causing the aerial or foliar blight. This disease is associated with the teleomorphase of R. solani AG-1 IA, the basidiomycete fungus Thanatephorus cucumeris. In this study, based on previous knowledge of the biology of R. solani AG-1 IA, two hypotheses were tested. In the first we postulated the occurrence of somatic incompatibility in populations of R. solani AG-1 IA. The second was that the population of R. solani AG1 IA from soybean has a clonal structure. Two population samples of R. solani AG-1 IA from soybean, obtained in Maranhão and Mato Grosso were analyzed. In the first sample, isolates with distinct RAPD (Random Amplified Polymorphic DNA) profile were selected to maximize the genetic diversity of isolates and to avoid the introduction of clones in the assay. The isolates were paired in all possible combinations in PDA plus charcoal medium and examined according to the resulting somatic interactions. Six somatic compatibility groups (SCG) were detected among 24 isolates of AG-1 IA. However, microscopic analyzes of the pairings indicated higher frequency of somatic incompatibility, resulting in the impossibility of grouping any two isolates of R. solani AG-1 IA into SCG. In general, the methodology for evaluating the macroscopic somatic interactions in PDA plus charcoal medium seemed not totally appropriate for discriminating between categories of somatic compatibility amongst isolates of R. solani AG-1 IA. With the second sample of isolates we aimed to determine the occurrence of clones in the population of the pathogen, i.e., isolates that share the same phenotypic RAPD profile and are somatically compatible. Considering the range of somatic interactions between pairings of R. solani AG-1 IA isolates and the deviations of the strict association between the GCS detected and the RAPD profile formerly observed by Fenille (11) and Meyer (20) are consistent with recombination. However, there is evidence for an expressive clonal component in the population. From a total of 43 isolates of R. solani AG-1 IA, 16 were probable clones.
Incompatibilidade somática em rhizoctonia solani ag-1 ia da soja
Keywords: Additional clonality; Population structure